Development of navigation system for visually impaired person - Shaha, Rajesh Kumar; Mahmud, Niaz; Bin Zafar, Ridwan; Rahman, Sraboni (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.